2021
DOI: 10.1002/adhm.202002070
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR‐Loaded Mesenchymal Stem/Stromal Cell Extracellular Vesicles Enhance Angiogenesis and Wound Healing

Abstract: Chronic wounds remain a substantial source of morbidity worldwide. An emergent approach that may be well-suited to induce the complex, multicellular processes such as angiogenesis that are required for wound repair is the use of extracellular vesicles (EVs). EVs contain a wide variety of proteins and nucleic acids that enable multifactorial signaling. Here, the capability of EVs is leveraged to be engineered via producer cell modification to investigate the therapeutic potential of EVs from mesenchymal stem/st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 61 publications
2
75
0
Order By: Relevance
“…As lyophilization adequately preserved the pro-angiogenic and anti-inflammatory capabilities of BDMSC EVs in vitro , we assessed whether these effects translated to a clinically relevant animal model. Previously, we demonstrated that BDMSC EVs loaded with the lncRNA HOTAIR enhanced wound closure after inducing an 8 mm punch biopsy on the dorsum of db/db mice, whereas unaltered BDMSC EVs did not [26]. Thus, we lyophilized HOTAIR-loaded BDMSC EVs and stored them at RT for 4 weeks, before reconstitution and usage in the same db/db mouse model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As lyophilization adequately preserved the pro-angiogenic and anti-inflammatory capabilities of BDMSC EVs in vitro , we assessed whether these effects translated to a clinically relevant animal model. Previously, we demonstrated that BDMSC EVs loaded with the lncRNA HOTAIR enhanced wound closure after inducing an 8 mm punch biopsy on the dorsum of db/db mice, whereas unaltered BDMSC EVs did not [26]. Thus, we lyophilized HOTAIR-loaded BDMSC EVs and stored them at RT for 4 weeks, before reconstitution and usage in the same db/db mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…BDMSCs were grown in EV-depleted media for 2 days before the conditioned medium was collected and subjected to differential ultracentrifugation with a 100,000 x g final centrifugation step as previously described [26]. Pelleted EVs were resuspended in 1x PBS and subsequently washed using Nanosep 300 kDa MWCO spin columns (Pall Laboratories; OD300C35).…”
Section: Ev Separationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, miRNA, siRNA or lncRNA can be loaded as cargo into the EVs. For example, EVs isolated from MSCs, which overexpressed lncRNA HOX transcript antisense RNA (HOTAIR), promoted angiogenesis and wound healing in diabetic mice [44]. In a study by Liu et al, it could be shown that the release of apoptotic bodies (a subgroup of EVs) by transplanted MSCs, led to the shift of macrophages towards an anti-inflammatory phenotype and promoted the healing of cutaneous wounds [45].…”
Section: The Role Of Mscs In Tissue Regenerationmentioning
confidence: 99%